2020
DOI: 10.1039/c9en00585d
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of zinc oxide and iron oxide engineered nanoparticles to Bacillus subtilis in river water systems

Abstract: Zinc oxide (nZnO) and iron oxide (nFeOx) engineered nanoparticles (ENPs) are widely used in consumer products and industrial applications, and consequently, are continuously being released into the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…[226] effects of two natural South African river water samples (Elands River (ER) and Bloubank River (BR)) on the toxicity of ENMs have been compared. [193] The results showed that high concentrations of ZnO NPs (100 and 1000 µg L −1 ) induced a significant reduction in the membrane integrity of Bacillus subtilis in ER, being absent for BR. They also found that γ-nFe 2 O 3 NPs showed no difference in both water samples, indicating that the unique physicochemical properties and substances of natural aqueous media may have distinct corona compositions on different ENMs, generating different outcomes.…”
Section: Magna Secreted Protein Cooh-ps Nps Nh 2 -Ps Npsmentioning
confidence: 94%
“…[226] effects of two natural South African river water samples (Elands River (ER) and Bloubank River (BR)) on the toxicity of ENMs have been compared. [193] The results showed that high concentrations of ZnO NPs (100 and 1000 µg L −1 ) induced a significant reduction in the membrane integrity of Bacillus subtilis in ER, being absent for BR. They also found that γ-nFe 2 O 3 NPs showed no difference in both water samples, indicating that the unique physicochemical properties and substances of natural aqueous media may have distinct corona compositions on different ENMs, generating different outcomes.…”
Section: Magna Secreted Protein Cooh-ps Nps Nh 2 -Ps Npsmentioning
confidence: 94%
“…The cell concentration was measured by counting the number of colony-forming units (CFUs) from the appropriate dilution on nutrient agar plates as previously described. 50 The viability of cells cultured with Fe NPs could also be evaluated by comparing it with control. 50 The experiments were conducted in triplicate.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…50 The viability of cells cultured with Fe NPs could also be evaluated by comparing it with control. 50 The experiments were conducted in triplicate.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In agriculture, research is in progress on the application of the antifungal properties of ZnO NPs to protect crops [ 307 , 310 ]. ZnO NPs are used in a broad range of commercial applications, thus it is important to understand their fate and behaviour in soil, water, their manner of absorption and spreading/accumulation in plants, animals and microorganisms, but also interactions with impurities [ 311 , 312 , 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 ]. It must be borne in mind that the dynamically increasing the commercial application of ZnO NPs without appropriate supervision and tests may contribute to their adverse impact on land and water plants and animals [ 335 , 336 ].…”
Section: Introductionmentioning
confidence: 99%